Evidence-Informed Policy-Making: Are We Doing Enough?; Comment on "Examining and Contextualizing Approaches to Establish Policy Support Organizations - A Mixed Method Study" - Moriah E. Ellen; Eliana Ben-Sheleg (Kerman University of Medical Sciences, 2022)
In their study of manifestations of policy support organizations (PSOs), Al Sabahi et al found that PSOs are united in their goal to support evidence-informed policy-making (EIPM), albeit with differing approaches. Their article is an important contribution to the body of research on evidence utilization and implementation. The unprecedented evidence climate presented by coronavirus disease 2019 (COVID-19) provides a unique window to motivate EIPM implementation. Research such as Al Sabahi and colleagues must prompt a dialogue regarding how best to address some of the current shortcomings in the field of EIPM. Monitoring and evaluation of best practices in EIPM is scarce. EIPM uptake is unsatisfactory, and the scientific community needs to ask itself why that is and what can be done. And, we should strive to develop a gradient that discerns between the convenient and the essential so countries can evaluate and pursue the policies to best address their greatest pain points through evidence.